Knowledge of Electric Cigarette Smoking Habits' Impact on Oral Health Among 18-20 Year-Olds at YARSI University - Alisa Novianty Pratiwi; Adinda Try Nuraisah; Chaerita Maulani (YARSI Dental Scientific Meeting - e Journal, 2025)
Introduction: The use of electric cigarettes among teenagers aged 18-20 years, has been increasing as a new trend. Although considered safer than conventional cigarettes, e-cigarettes still contain harmful substances that can damage health, particularly oral health. Teenagers’ knowledge about the dangers of electric cigarettes is still lacking. It is essential to raise awareness among teenagers regarding the effects of e-cigarette usage on oral health. Objective: To examine the level of knowledge of the impact of electric cigarette smoking habits' impact on oral health and the relationship between sociodemographic factors, among the age group of 18-20 years at YARSI University. Material and Methods:  This research is analytical with a cross-sectional design, involving 368 respondents selected through purposive sampling. Data were collected using a questionnaire on knowledge about the impact of electric cigarette smoking on oral health and analyzed with Spearman's correlation and Chi-Square tests. Results: The results showed that the majority of respondents had a moderate level of knowledge, and there was a significant relationship between some sociodemographic factors and the respondents' level of knowledge (p<0.05). Discussion: The majority of electric cigarette user groups have a high level of knowledge and come from families with high socioeconomic conditions. This factor influences their lifestyle, which tends to follow trends using e-cigarettes. Conclusion: Despite possessing moderate knowledge regarding the adverse effects of electric cigarette use on oral health, the majority of respondents persist in their consumption.